Quantitative in situ measurement of estrogen receptor mRNA predicts response to tamoxifen. - Jennifer M Bordeaux (Public Library of Science (PLoS), 2012)
Purpose Quantification of mRNA has historically been done by reverse transcription polymerase chain reaction (RT-PCR). Recently, a robust method of detection of mRNA utilizing in situ hybridization has been described that is linear and shows high specificity with low background. Here we describe the use of the AQUA method of quantitative immunofluorescence (QIF) for measuring mRNA in situ using ESR1 (the estrogen receptor alpha gene) in breast cancer to determine its predictive value compared to Estrogen Receptor α (ER) protein. Methods Messenger RNA for ER (ESR1) and Ubiquitin C (UbC) were visualized using RNAscope probes and levels were quantified by quantitative in situ hybridization (qISH) on two Yale breast cancer cohorts on tissue microarrays. ESR1 levels were compared to ER protein levels measured by QIF using the SP1 antibody. Results ESR1 mRNA is reproducibly and specifically measurable by qISH on tissue collected from 1993 or later. ESR1 levels were correlated to ER protein levels in a non-linear manner on two Yale cohorts. High levels of ESR1 were found to be predictive of response to tamoxifin. Conclusion Quantification of mRNA using qISH may allow assessment of large cohorts with minimal formalin fixed, paraffin embedded tissue. Exploratory data using this method suggests that measurement of ESR1 mRNA levels may be predictive of response to endocrine therapy in a manner that is different from the predictive value of ER.